A Reflective Account of Character-Based Professional Learning in Higher Education - Ashley Brandon; Emily Farkas (Journal of Scholarly Engagement)
This manuscript will reflect on the planning and development of professional learning opportunities provided to diverse university stakeholders on character education and virtue formation. While reflecting on the approach to the project, planning logistics and content development are explored explicitly. An evaluation exploring training modalities, attendance, arrangement, and feedback were used to gain insight and guide the authors in their reflective practice. The reflective narrative and evaluation of ideas led to a decision about the factors that aided the project’s implementation. In future professional learning opportunities, determining attendees’ prior knowledge of the content and additional internal support for communication and development plans is key. While evaluating how to implement professional learning opportunities focused on character, the planning and development process were explored; in coming to a decision, the reflective criteria of responsibility, open-mindedness, and wholeheartedness were focal points.